Endovascular treatment of acute ischemic stroke in patients with pre-morbid disability: a meta-analysis. (15th March 2022) - Bala, Fouzi; Beland, Benjamin; Mistry, Eva; Almekhlafi, Mohammed A; Goyal, Mayank; Ganesh, Aravind
Abstract : Background: Trials of endovascular thrombectomy (EVT) for acute stroke have excluded patients with pre-morbid disability. Observational studies may help inform consideration of EVT in this population. We aimed to assess the effectiveness and safety of EVT in patients with pre-morbid disability. Methods: According to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we searched MEDLINE and Embase for studies describing outcomes in patients with pre-morbid disability (modified Rankin Scale (mRS) 2–5), treated with EVT or medical management (MM). Random-effects meta-analysis was used to pool outcomes including 90-day return to baseline mRS, symptomatic intracerebral hemorrhage (sICH), and 90-day mortality. Results: We analyzed 14 studies of patients with pre-morbid disability (mRS 2–5, 1373 EVT and 253 MM). The rate of return to baseline mRS was 30.0% (95% CI 25.3% to 34.7%) in patients treated with EVT. Compared with medical therapy, EVT was associated with a higher likelihood of return to baseline mRS (OR 2.37, 95% CI 1.39 to 4.04) and a trend towards lower mortality (OR 0.68, 95% CI 0.46 to 1.02), with similar odds of sICH (OR 1.01, 95% CI 0.49 to 2.08). In studies comparing patients with versus without pre-morbid disability treated with EVT, similar results were found except that pre-morbid disability, when defined more strictly as mRS 3–5, was associated with mortality (OR 3.49, p<0.001). Conclusion: In eligible patients with pre-morbid disability, observational studies suggest that EVT carries a higher chance of return to baseline mRS compared with patients treated with MM or without pre-morbid disability, although with higher mortality than patients without pre-morbid disability. These findings argue against the routine exclusion of such patients from EVT and merit validation with randomized trials.